2008
DOI: 10.2320/matertrans.maw200804
|View full text |Cite
|
Sign up to set email alerts
|

High Strength and Fracture Toughness Balances in Extruded Mg-Zn-RE Alloys by Dispersion of Quasicrystalline Phase Particles

Abstract: Six kinds of Mg-2.5 at%Zn-0.5 at%RE (RE: rare earth element, Y, Gd, Tb, Dy, Ho and Er) alloys with grain size of 1$2 mm and containing a quasicrystalline icosahedral phase were prepared by casting and extrusion. These alloys had high strength and high fracture toughness balances, due to the synergetic effect of grain refinement and the dispersion of quasicrystalline phase particles. Microstructural observations showed a ductile fracture pattern, and that the origin of void nucleation was not the quasicrystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…3,4) Fine grained structures have been successfully achieved by applying various techniques, e.g. ECAP (Equal-channel angular pressing) 5,6) and RCP (Roll Compaction process).…”
Section: Introductionmentioning
confidence: 99%
“…3,4) Fine grained structures have been successfully achieved by applying various techniques, e.g. ECAP (Equal-channel angular pressing) 5,6) and RCP (Roll Compaction process).…”
Section: Introductionmentioning
confidence: 99%
“…23) A previous study also confirmed that grain boundary sliding is the dominant deformation mechanism at the temperature of 573 K using the MgZnY alloy with a grain size of less than 10 µm. 25) On the other hand, the quasicrystal phase has the role of creating the pinning effect during the deformation at not only room temperature 11) but also at even elevated temperatures, i.e., superplastic regime. 25) However, these previous fracture surface observations show that the quasicrystal phase is not the origins of the crack propagation site in the fatigue tests 26) and the micro-void nucleation site in the toughness tests 11) due to the strong matching between the quasicrystal phase and the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties of Alloy 1 and Alloy 2 are summarized in Table 1, while the previous data of the Mg-Zn-RE alloys after conventional extrusion [15][16][17][18][19][20] are also listed in Table 1 for comparison. It can be seen that the present study shows superior mechanical properties to those of previous conventionally extruded Mg-Zn-RE alloys.…”
Section: Microstructure and Phase Constitution Of The Alloys Before Ementioning
confidence: 99%